Strategic exploitation of a common resource under environmental risk - FESSELMEYER, Eric (Institutional Knowledge at Singapore Management University, 2013)
We study the effect of environmental risk on the extraction of a common resource. Using a dynamic and non-cooperative game in which an environmental event impacts the renewability and the quality of the resource, we show that the anticipation of such an event has an ambiguous effect on extraction and the tragedy of the commons. A risk of a reduction in the renewability induces the agents to extract less today while a risk of a deterioration in the quality has the opposite effect. Moreover, when environmental risk induces conservation, the tragedy of the commons is worsened. (C) 2012 Elsevier B.V. All rights reserved.